Mekanisme Adopsi QRIS di Retail: Studi Empiris atas Fleksibilitas, Efisiensi Waktu, dan Protektivitas dalam Meningkatkan Transaksi Digital - Muhammad Hilmansyah Lukman; Dafin Firmansyah; Denada Nandini; Mochammad Zahid Khairu Ghani; Zelda Saleha Fermana; Syti Sarah Maesaroh (Lembaga Pengembangan Kinerja Dosen, 2025)
The advancement of digital technology in financial systems, including the implementation of QRIS (Quick Response Code Indonesian Standard) in the retail sector, has driven the increased use of non-cash payment methods. How flexibility, time efficiency, and protectivity influence the number of QRIS transactions conducted in retail stores is the subject of this research. Validity, reliability, classical assumption analysis, and hypothesis analysis. Results show that time efficiency contributes significantly to increasing QRIS transactions, while flexibility and security are not significantly affected. Only 18.9% of the variation in QRIS usage behavior is caused by the three independent variables, according to the coefficient of determination (R2). These findings indicate that time efficiency is a key factor in driving the retail sector to adopt digital payment systems.